The Influence of Financial Literacy on Youth Entrepreneurship in Developing Countries - Stefano Battiston; Giovanna Vicarelli; Luigi Guiso (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This paper explores sustainable tourism practices in Southeast Asia, focusing on the interplay between economic growth and environmental conservation. The study employs a case study approach to assess the effectiveness of eco-tourism initiatives in Thailand, Indonesia, and Malaysia. Findings indicate that community-based tourism and stringent environmental regulations are key to achieving sustainability. Policy implications for government and industry stakeholders are discussed.